Demonstração do resultado econômico: um estudo sobre a eficiência na aplicação dos recursos públicos em uma universidade pública federal do semiárido potiguar - Ribeiro, Ranieire Paula (Universidade Federal Rural do Semi-Árido, 2018)
In public administration it is important to apply the resources efficiently. Thus, the aim of this research is to analyze if the Federal University of Rural Semiarid (Universidade Federal Rural do Semi-Árido - UFERSA) is applying the public resources efficiently on the undergraduate courses that are part of the Humanities and Applied Social Sciences Center (Centro de Ciências Sociais Aplicadas e Humanas - CCSAH), through the Economic Income Statement. The research was developed through the exploratory, descriptive, applied, bibliographical and documental methodologies. A case study was also carried out. Data analysis was performed through qualitative research. In order to achieve our goal, the public services costs model proposed by Santos (2014) was used to find the costs of the undergraduate courses offered at UFERSA, in Mossoró (RN/Brazil). After data collection, it was possible to calculate the economic result of UFERSA’s CCSAH undergraduate courses through the Economic Income Statement. The results of the survey verified, after determining the costs, the data showed that the Veterinary Medicine course was the one with the highest costs while the Rural Education course presents the lowest costs among the undergraduate courses of the campus, being the quantity of students the key factor of this result. The economic income calculated to the Business, Accounting Sciences and Law courses presented, in 2017, negative economic results, thus being economically inefficient. Considering that the efficiency evaluation with only quantitative data was insufficient, the study also included the analysis of qualitative data. The results of exams like the Brazilian National Exam of Students Performance (ENADE), the Exam of Sufficiency of the Federal Accounting Council and the exam of the Brazilian Bar Association, all related to the courses that presented negative economic results, were compared to the results obtained by the same courses offered by universities and faculties of the private sector and UFERSA’s students presented a better performance when compared to the students of these private courses. These data show that despite the economic inefficiency, when it comes to the qualitative aspects, the courses presented a better performance, what is the result of teaching quality and the investment of public resources
Keywords: Eficiência; Custos; Demonstração do Resultado Econômico; Efficiency; Costs; Economic Income Statement; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA